Reducing Internet Gambling Harms Using Behavioral Science: A Stakeholder Framework - Gainsbury, Sally M.; Black, Nicola; Blaszczynski, Alex; Callaghan, Sascha; Clancey, Garner; Starcevic, Vladan; Tymula, Agnieszka (Frontiers in Psychiatry, 2020)
Internet gambling provides a unique environment with design mechanics and data-driven opportunities that can impact gambling-related harms. Some elements of Internet gambling including isolation, lack of interruption, and constant, easy access have been argued to pose specific risks. However, identifiable player accounts enable identification of behavioural risk markers and personalised private interfaces to push customised messages and interventions. The structural design of the Internet gambling environment (website or app) can have a strong influence on individual behaviour. However, unlike land-based venues, Internet gambling has few specific policies outlining acceptable and unacceptable design practices. Harm minimisation including responsible gambling frameworks typically include roles and responsibilities for multiple stakeholders including individual users, industry operators, government regulators, and community organisations. This paper presents a framework for how behavioural science principles can inform appropriate stakeholder actions to minimise Internet gambling-related harms. A customer journey through internet gambling demonstrates how a multidisciplinary nexus of collaborative effort may facilitate a reduction in harms associated with Internet gambling for consumers at all stages of risk. Collaborative efforts between stakeholders could result in the implementation of appropriate design strategies to assist individuals to make decisions and engage in healthy, sustainable behaviours.